The Mediator Role of Depression, Stress and Anxiety in the Relationship between Childhood Trauma Experiences and Psychological Vulnerability - YÜKSEL, MÜGE (My University, 2024)
The aim of this study was to examine the mediating role of stress, anxiety and depression in the relationship between psychological vulnerability and childhood trauma experiences among university students. For this purpose, structural equation model was used in the study. A total of 465 students, including 329 (70.01%) females and 139 (29.9%) males, were selected using the random disproportionate cluster sampling method. In the study, data were collected using Psychological Vulnerability Scale, Childhood Trauma Scale, Depression-Anxiety-Stress Scale Short Form (DASS-21) with personal information form. Analyses were carried out using AMOS 20.0 and SPSS 20 programmes. The data obtained as a result of the study were tested with the structural equation model. Examining the model established between psychological vulnerability, childhood trauma experiences, stress, depression and anxiety scores, it was found that anxiety, stress and depression have a mediating role in the relationship between childhood trauma experiences and psychological vulnerability.Keywords: Psychological vulnerability, childhood trauma, anxiety, depression, stress, structural equation model
Keywords: Psychological vulnerability; childhood trauma; anxiety; depression; stress; structural equation model